Gastroepiploic vascularized lymph node transfer for extremities' lymphedema: Is two better than one? A retrospective case-control study. Issue 9 (September 2022) - Elia, R; Chen, HC; Taranto, G Di; Ciudad, P; Torto, F Lo; Nacchiero, E; Giudice, G; Maruccia, M
Summary: Single (SG-VLN) and double gastroepiploic vascularized lymph node transfer (DG-VLN) have shown promising results for the treatment of extremities' lymphedema. The literature search yields only few other cases describing outcomes following double VLN transfers, but no comparative studies have been produced so far. The aim of this study was to retrospectively examine and compare the effects of SG-VLN versus DG-VLN transfer. All patients diagnosed with extremities' stage II and III lymphedema who had undergone SG-VLN or DG-VLN between January 2012 and December 2018 were identified from two institutions' databases. Demographic and surgical data were collected. The primary endpoint was the comparison of the reduction in limb circumference (CRR) within 12 months post-surgery. Secondary endpoints included the reduction of cellulitis episodes and patients' quality of life improvement. Eighty-nine patients met the inclusion criteria. At 12 months of follow-up, higher CRR values were observed in the double inset group (p<0.05*) both at above elbow/above knee (AE/AK) level (SG-VLN: 70.6% ± 0.6%; DG-VLN: 72.2% ± 0.7%) and at below elbow/below knee level (SG-VLN: 59.1% ± 1.3%; DG-VLN: 61.6% ± 3.7%). Subgroup analyses of the involved limb (upper vs lower) were consistent with the primary treatment effects. The reduction of cellulitis episodes did not differ between the two groups, while the DG-VLN group showed better results in the overall satisfaction function, symptoms, and mood domains of the LYMQoL questionnaire (p=0.04). The study suggests that either single or double transfer can produce excellent results, but double inset of the gastroepiploic VLNT flap may produce greater volume reductions both at 12 and 24 months. Further studies with a larger sample size are warranted to corroborate our results.